( f ∘ g ) ( x ) is equivalent to f ( g ( x ) ) . We solve this problem just as we solve f ( x ) . But since it asks us to find out f ( g ( x ) ) , in f ( x ) , each time we encounter x, we replace it with g ( x ) . In the above problem, f ( x ) = x + 3 . Therefore, f ( g ( x ) ) = g ( x ) + 3 . ⇒ ( f ∘ g ) ( x ) = 2 x − 7 + 3 ⇒ ( f ∘ g ) ( x ) = 2 x − 4 Basically, write the g ( x ) equation where you see the x in the f ( x ) equation. f ∘ g ( x ) = ( g ( x ) ) + 3 Replace g ( x ) with the equation f ∘ g ( x ) = ( 2 x − 7 ) + 3 f ∘ g ( x ) = 2 x − 7 + 3 we just took away the parentheses f ∘ g ( x ) = 2 x − 4 Because the − 7 + 3 = 4 This is it g ∘ f ( x ) would be the other way around g ∘ f ( x ) = 2 ( x + 3 ) − 7 now you have to multiply what is inside parentheses by 2 because thats whats directly in front of them. g ∘ f ( x ) = 2 x + 6 − 7 Next, + 6 − 7 = − 1 g ∘ f ( x ) = 2 x − 1
I could better help if I knew the question.....
Answer:
The answer is 166/21, or 7 19/21
Step-by-step explanation:
First, you would set up the equation, which is:
13 1/7 - 5 5/21
Next, you would turn them into an improper fraction, which is:
92/7 - 110/21
Then, you would multiply 92/7 by 3/3 because that is the least common multiple for 21 and 7 (which are the denominators). When you are done multiplying, the equation would be:
276/21 - 110/21
Afterwards, you would subtract the numerators and leave the denominators alone, which gives you the answer 166/21. As a mixed number, this would equal 7 19/21.
Answer:
See below.
Step-by-step explanation:
So we started off with the equation:
![x+y=2](https://tex.z-dn.net/?f=x%2By%3D2)
And we subtracted x from both sides to acquire:
![y=2-x](https://tex.z-dn.net/?f=y%3D2-x)
Now, this is essentially slope-intercept form. Recall that the slope-intercept form is:
![y=mx+b](https://tex.z-dn.net/?f=y%3Dmx%2Bb)
Where m is the slope and b is the y-intercept.
If we rearrange our equation:
![y=2-x\\y=-x+2](https://tex.z-dn.net/?f=y%3D2-x%5C%5Cy%3D-x%2B2)
And put some parentheses:
![y=(-1)x+(2)](https://tex.z-dn.net/?f=y%3D%28-1%29x%2B%282%29)
We can see that this is indeed slope-intercept form.
And we can see that m is -1 and b is 2.
In other words, the slope is -1 and the y-intercept is 2.
<em><u>The equivalent expressions are:</u></em>
![7(-\frac{3}{4}x - 3) = (7 \times \frac{-3}{4}x) + (7 \times -3)\\\\7(-\frac{3}{4}x - 3) = \frac{-21x}{4} - 21](https://tex.z-dn.net/?f=7%28-%5Cfrac%7B3%7D%7B4%7Dx%20-%203%29%20%3D%20%287%20%5Ctimes%20%5Cfrac%7B-3%7D%7B4%7Dx%29%20%2B%20%287%20%5Ctimes%20-3%29%5C%5C%5C%5C7%28-%5Cfrac%7B3%7D%7B4%7Dx%20-%203%29%20%3D%20%5Cfrac%7B-21x%7D%7B4%7D%20-%2021)
<em><u>Solution:</u></em>
<em><u>Given expression is:</u></em>
![7(-\frac{3}{4}x - 3)](https://tex.z-dn.net/?f=7%28-%5Cfrac%7B3%7D%7B4%7Dx%20-%203%29)
We have to find the equivalent expressions
By distributive property,
a(b + c) = ab + ac
Therefore,
![7(-\frac{3}{4}x - 3) = (7 \times \frac{-3}{4}x) + (7 \times -3)\\\\7(-\frac{3}{4}x - 3) = \frac{-21x}{4} - 21](https://tex.z-dn.net/?f=7%28-%5Cfrac%7B3%7D%7B4%7Dx%20-%203%29%20%3D%20%287%20%5Ctimes%20%5Cfrac%7B-3%7D%7B4%7Dx%29%20%2B%20%287%20%5Ctimes%20-3%29%5C%5C%5C%5C7%28-%5Cfrac%7B3%7D%7B4%7Dx%20-%203%29%20%3D%20%5Cfrac%7B-21x%7D%7B4%7D%20-%2021)
Thus equivalent expressions are found